2018
DOI: 10.1002/ajb2.1153
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of root apical meristem structures in vascular plants: plasmodesmatal networks

Abstract: Irrespective of their diversified structures, the RAMs of vascular plants can be classified into two types with respect to PNs: the fern (monilophyte) type, which has a lineage-specific PN with only primary PD, and the seed-plant type, which has an interspecific PN with secondary PD in addition to primary PD. PNs may have played a key role in the evolution of apical meristems in vascular plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…These data suggested that meristem organisation is strikingly similar between RAMs and SAMs and that they share common developmental mechanisms for dichotomous branching. Similarity in plasmodesmatal density also suggested that basic cellular characteristics are shared between RAMs and SAMs in L. clavatum (Imaichi & Hiratsuka, 2007; Imaichi et al ., 2018). It has been proposed that lycophyte roots may have evolved from the rooting axes of Early Devonian Drepanophycales or zosterophylls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that meristem organisation is strikingly similar between RAMs and SAMs and that they share common developmental mechanisms for dichotomous branching. Similarity in plasmodesmatal density also suggested that basic cellular characteristics are shared between RAMs and SAMs in L. clavatum (Imaichi & Hiratsuka, 2007; Imaichi et al ., 2018). It has been proposed that lycophyte roots may have evolved from the rooting axes of Early Devonian Drepanophycales or zosterophylls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Upon entering the EDZ, we detected a clear concentric organization of the cell layer and each one of these displayed specific traits, which allows the distinction from one another (Figure 7C, right). The diverse set of features analyzed in the EDZ of Ceratopteris roots seems to be conserved with other vascular plants [32,41,56,68,[72][73][74][75][76][77]. This could imply that some cell lineages already existed in the common ancestor of euphyllophytes and suggests the conservation of genetic networks involved in their specification, to some extent, between ferns and seed plants.…”
Section: Ceratopteris Root Cell Layers Exhibit the Conservation Of Specific Traitsmentioning
confidence: 94%
“…Even though this type of meristem may not fit into the idea of a multicellular meristem, it is because this current concept is based on angiosperms. More evidence about meristem dynamics has been obtained by exploring plant diversity and understanding how this essential part of the plant is functioning in extant lineages [65][66][67][68]. Additionally, the meristem organization in Ceratopteris roots is highly conserved in roots of different fern species (Figure 1B, Table S1).…”
Section: Ceratopteris Root Cell Layers Exhibit the Conservation Of Specific Traitsmentioning
confidence: 99%
“…The symplastic movement of SHR is conserved among several angiosperms and even expanded to other cell layers in the root; nevertheless, the assessment of CriSHR protein moving through Ceratopteris root tissues would be interesting since a high number of plasmodesma connections have been detected in the root meristems of ferns. In addition, the conservation of CriSCR-CriSHR interaction needs to be tested in order to understand if their physical interaction has been preserve during evolution (Cui et al, 2007;Henry et al, 2017;Imaichi et al, 2018;Xiao et al, 2019;Dong et al, 2021;Kajala et al, 2021). In general, the conservation of all these genes, i.e., SCR, SHR, and RBR, and their expression in the root tip, may indicate a similar role of this whole gene circuit as observed in seed plants.…”
Section: The Evolution Of the Cycd-rbr-scr-shr Networkmentioning
confidence: 99%